A specific cognitive behavioral group therapy program for stimulant use disorder - Karsinti, Emily; Vorspan, Florence; Therribout, Norman; Icick, Romain; Bloch, Vanessa; Fortias, Maeva; Piani, Kristel; Romo, Lucia (Frontiers in Psychiatry, 2022)
Introduction: Stimulant use is an important health issue. In the US in 2018, 2.8% of males and 1.5% of females older than 18 had used cocaine in the preceding 12 months (Cano et al., 2020). Objective: To intervene in a specific targeted group of Stimulant Use Disorder (SUD) patients according to CBT and relapse prevention theories, and to determine the program’s feasibility and attendance. Method: SUD patients in addiction care were evaluated for addictive, psychological and psychiatric dimensions at baseline and conclusion in a 9-session CBT group program with several themes: define SUD, enhance motivation, involve close companions, cope with craving, decline a proposal, solve problems, invite expert patients, invest time and money, and review content. Results: 41 patients attended at least one session. They were mainly poly-dependent, primarily cocaine users. Sixty percent of the population also suffered from another psychiatric comorbidity. Median attendance for participants was 7/9 sessions. Conclusion: A specific targeted CBT group for stimulant dependent highly comorbid patients is feasible. These findings suggest that peers should be included in addiction care services.